Late Holocene volcanic and human impacts on the mountain vegetation in central Sumatra, Indonesia. (10th June 2022) - Willkomm, Natascha; Setyaningsih, Christina Ani; Saad, Asmadi; Sabiham, Supiandi; Sauer, Daniela; Behling, Hermann
Abstract: The Kerinci Seblat National Park (KSNP) has been a region of great significance for palynological studies featuring the combination of unique tropical vegetation, tectonics determining frequent volcanic eruptions, and a long settlement history. This palynological study aims at reconstructing ecosystem processes and is based on a long-term analysis of vegetation composition in the mountainous region of Sumatra. The research question focused on the influence of natural disturbance such as climate and volcanism, and anthropogenic impacts and fire on vegetation dynamics in the KSNP in the Sumatran highlands. A 2300-year-old lake sediment record of Danau Belibis at 2078 m asl. provides insights into the changes in vegetation composition over time in a mountainous tropical rainforest region in Jambi province. Over the entire record, Taxus was the most dominant genus. Volcanic eruptions caused continuous competition between volcanophile taxa like Casuarina and Myrica, and primary forest taxa. Settlements and agricultural activity are represented throughout the whole record. Forest clearings for wood exploitation and cultivation took place in the period from 1600 to 1000 years BP and from 600 years BP to the present. Crops were already introduced at the beginning of the record in the Kerinci highland region. The charcoal record illustrates only occasional fire events caused by natural forces. Our findings refer to the vulnerability of vegetation dynamics concerning important environmental drivers and suggest volcanic events as an important factor for environmental changes in the highlands of Sumatra.